Association between oropharyngeal microbiome and weight gain in piglets during pre and post weaning life - Andrew Wange Bugenyi; Ho-Seong Cho; Jaeyoung Heo (Journal of Animal Science and Technology, 2020)
Birth weight and subsequent weight gain is of critical importance in the survival and performance of piglets on a commercial swine farm setting. Oropharyngeal microbiome could influence immunity, and feeding behavior thus impacting health and weight gain. We used 16S rRNA gene sequencing to profile the composition and predicted metabolic functionality of the oropharyngeal microbiota in 8 piglets (4 with a birthweight ≤ 1.0 kg and 4 with a birthweight ≥ 1.7 kg) at 11, 26, and 63 days of age. We found 9 genera that were significantly associated with average daily gain (ADG) at 11 days (false discovery rate, FDR < 0.05) and 26 days of age (FDR < 0.1), respectively. The microbial functional profile revealed several pathways associated with ADG (FDR < 0.05). Among these, pathways related to degradation of catechols showed a positive association with ADG at 11, 26, and 63 days of age, implying a potential to breakdown the host-derived catecholamines. We also noted that pathways related to the biodegradation of nucleosides and nucleotides increased with ADG during the pre-weaning phase, while those involved in their biosynthesis decreased. Our findings provide insights into the oropharyngeal microbial memberships and metabolic pathways that are involved in a piglet’s weight gain. Thus, providing a basis for the development of strategies aimed at improving weight gain in pigs.